Delphi Approach to explore ways to optimize case manager services in inpatient wards of Sanglah General Hospital - Sayu Kade Alit Sagitariani; Pande Putu Januraga; I Ketut Surya Negara (Universitas Udayana, 2020)
Background and purpose: Case manager services in inpatientrooms have gained popularity in many hospitals in Indonesia,however there are challenges in its implementation. This study aims to explore ways to optimize the characteristics of the case manager, case management practice and outcome of the case manager in cases in inpatient wards based on the Sanglah Hospital standards. Methods: The study utilized a two-stage Delphi study design,started with a qualitative data collection and followed by aquantitative survey. Data collection was done in May-June 2020 based on the concept of case manager characteristics, practice and outcomes. The qualitative data collection through in-depth interviews involved 9 key informants. It aimed to explore case manager services based on qualifications, competencies, ethical standards, workload, hierarchy and guidelines, implementation of case management and indicators of effectiveness of case management at Sanglah General Hospital. The results of the indepth interviews with thematic analysis informed the Delphi survey instrument development. The Delphi survey aimed to generate agreement on the characteristic of the case manager, case management practice and outcome of the case manager among 21 expert panelists (case managers) in the inpatient wards of Sanglah Hospital. This Delphi survey was conducted in 3 rounds, the results were analyzed based on the median value and quartile deviation (QD). Results: The three rounds of the Delphi survey showed that there was an agreement regarding the qualifications of the case manager, competency development, mechanism for appointment and placement of case managers, case manager guidelines, organizational structure, job descriptions and authorities, information of the presence and role of case managers, screening indicators according to characteristics of inpatient cases, case management target measurement tools, case manager service evaluation indicators as well as the activity feedback loop. Conclusion: Optimization of the case manager service should focus on aspects of human resources, developing guidelines and work systems as well as evaluation indicators and feedback mechanism.